The Effect of Motivation and Demotivation through Social Media Facilities on Improving the Quality of Generation-Z Human Resources in Tambak Oso Village - M. Farhan Alfarisi; Suwaji, Rifiki (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This research aims to analyze the influence of motivation and demotivation through social media on the quality improvement of Generation Z human resources in Tambak Oso Village, Sidoarjo. As digital platforms become integral to daily life, Generation Z who are highly exposed to online content are simultaneously influenced by both motivational and demotivational material. The study uses a quantitative approach with a survey method, involving 55 respondents selected through purposive sampling. Data collection was conducted using questionnaires and analyzed through multiple linear regression using SPSS version 21. The findings reveal that motivational content, such as educational messages, self-improvement narratives, and inspirational media, significantly affects the development of Generation Z’s personal and professional attributes. Demotivational content such as hate speech, cyberbullying, and negative comparisons also impacts development, albeit to a lesser extent. The results of the t-test indicate that both motivation (p = 0.001) and demotivation (p = 0.040) have partial effects on the quality of human resources. The F-test results (p = 0.001) further confirm that both variables together have a simultaneous effect. The coefficient of determination (R² = 0.224) suggests that 22.4% of the variance in human resource quality is explained by these two variables. This study highlights the importance of digital literacy, emotional readiness, and strategic policy to ensure that social media becomes a constructive tool in shaping the future of Generation Z. Educational institutions and local governments are encouraged to promote motivational digital content while mitigating exposure to negative influences through media education and community engagement.